Produção e análise físico-química de leite in natura em período de seca na região de Avaré, São Paulo, Brasil - Bacciotti, Anderson; Santiago, Karina Basso [UNESP]; Augusto, Ricardo Sgarbi; Soares, Vanessa Mendonça [UNESP]; Pereira, Juliano Gonçalves [UNESP]; Martins, Otávio Augusto [UNESP]; Biondi, Germano Francisco [UNESP] (My University, 2010)
The objective is to assess physically and chemically the milk production of five producers, based on animal nutrition during the dry period in the region of Avaré, São Paulo, Brazil. Physico-chemical analysis were acidity, fat, total solids, solids, temperature, relative density at 15oC, cryoscopic index and volume of milk produced per day. The physical-chemical analysis showed no changes in accordance with Normative Instruction 51/02, Ministry of Agriculture, Livestock and Supply (MAPA), Brazil. Based on these results, it can be concluded that the milk produced by five producers, with a different diet for a period of drought, have a good physical and chemical quality for human consumption.

O objetivo consiste em avaliar física e quimicamente a produção de leite de cinco produtores, com base na alimentação dos animais, no período de seca, na região de Avaré, São Paulo, Brasil. As análises foram físico-química foram a acidez, gordura, extrato seco total, extrato seco desengordurado, temperatura, densidade relativa a 15oC, índice crioscópico e o volume de leite produzido por dia. As análises físico-químicas não apresentaram alterações de acordo com a Instrução Normativa 51/02, do Ministério da Agricultura, Pecuária e Abastecimento (MAPA). Com base nesses resultados, pode-se concluir que os leites produzidos pelos cinco produtores, com uma dieta diferenciada num período de estiagem, apresentam uma boa qualidade físico-química para o consumo humano.
Production and physico-chemical analysis of in natura milk in the dry season in the region of Avaré, São Paulo, Brazil
Keywords: Analysis; Physical-Chemical; Milk; Food; Análises; Físico-química; Leite; Alimentação